2014
DOI: 10.5194/amt-7-1075-2014
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of characteristic parameters for water vapour transmittance in the development of ground-based sun–sky radiometric measurements of columnar water vapour

Abstract: Abstract. Sun-sky radiometers are instruments created for aerosol study, but they can measure in the water vapour absorption band allowing the estimation of columnar water vapour in clear sky simultaneously with aerosol characteristics, with high temporal resolution. A new methodology is presented for estimating calibration parameters (i.e. characteristic parameters of the atmospheric transmittance and solar calibration constant) directly from the sun-sky radiometer measurements. The methodology is based on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(59 citation statements)
references
References 19 publications
(21 reference statements)
4
55
0
Order By: Relevance
“…Several methodologies have been recently developed in order to obtain accurate estimations: Global Navigation Satellite System (GNSS), including the Global Positioning System (GPS) (Bevis et al, 1992;Guerova et al, 2016), microwave radiometers (Elgered et al, 1982) and sun photometers (Campanelli et al, 2014;Halthore et al, 1997;Alexandrov et al, 2004) are the automatic remote sensing instruments able to provide precise and frequent measurements of W . All of them have some pros and cons.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several methodologies have been recently developed in order to obtain accurate estimations: Global Navigation Satellite System (GNSS), including the Global Positioning System (GPS) (Bevis et al, 1992;Guerova et al, 2016), microwave radiometers (Elgered et al, 1982) and sun photometers (Campanelli et al, 2014;Halthore et al, 1997;Alexandrov et al, 2004) are the automatic remote sensing instruments able to provide precise and frequent measurements of W . All of them have some pros and cons.…”
mentioning
confidence: 99%
“…Finally, the relatively low cost and easy deployment of sun photometers allowed the establishment of several international networks in the last 30 years worldwide. AErosol RObotic NETwork (AERONET) network (Holben et al, 1998;Smirnov et al, 2004), Global Atmospheric Watching Precision Filter Radiometer (GAW-PFR) network (Wehrli, 2000;Nyeki et al, 2005) and European Skynet Radiometers (ESR-SKYNET) network (Campanelli et al, 2012(Campanelli et al, , 2014 provide operationally free estimation of W or develop algorithms and open-source packages for improving the retrieval of this important atmospheric pa- rameter. However, the great problem of this methodology is the estimation of the sun-photometric calibration parameters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other sun photometers such as precision filter radiometers (PFRs) (Nyeki et al, 2005) have also been used by the Global Atmosphere Watch (GAW) WMO programme to monitor IWV. Furthermore, the SKYNET radiometer network (details at http://atmos2.cr.chiba-u.jp/skynet/) also retrieves IWV using Prede-POM sun photometers at many stations (Campanelli et al, 2012(Campanelli et al, , 2014. Finally, national networks of sun photometers that are installed and operating in some countries also provide integrated water vapour (IWV) retrievals; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…CIMEL, PREDE-POM, MFR) have also been used to calculate water vapour transmittance and thus estimate IWV. Filter radiometer recordings in the spectral region around water vapour absorption bands in the near-infrared region are used to calculate this quantity (Halthore et al, 1997;Campanelli et al, 2018;Nyeki et al, 2005). The World Meteorological Organization (WMO) recommends the use of spectral windows centred around 719, 817 and 946 nm, though the most frequently used is the 946 nm bandpass, which Ingold et al (2000) showed provides the most robust results.…”
Section: Introductionmentioning
confidence: 99%